A multivariate characterization of productive-reproductive efficiency and age at first calving in Holstein cows - Marini, Pablo Roberto; Biga, Pablo; Di-Masso, Ricardo (Agronomía Mesoamericana, 2021)
Introduction. The evaluation of productive efficiency must be accompanied by comprehensive indicators to assess the behavior of dairy cows in grazing systems. Objective. To identify in a herd of Holstein dairy cows grouped by age at first calving, those with the highest efficiency in grazing systems, based on a multivariate characterization of productive and reproductive indicators. Materials and methods. Retrospective data from 1785 primiparous cows of the Holstein breed, registered between the years 1999-2016 in two commercial establishments belonging to the Los Angeles-Argentina company, were used. Cows were categorized into three groups according to their age at first calving: Group 1 - 750 days, Group 2 - 840 days, and Group 3 - 1098 days. The variables total productive life, total milk production, milk index, and average calving interval were used associated with the age at first calving using the multivariate principal components technique. Results. No groupings associated with age group at first birth were observed. The two first principal components explained 92.9 % of the total variance observed. It was possible to define four quadrants representing all the combinations between the positive and negative values. Cows distribution of the three groups in the four quadrants was homogeneous (x2=6.291; p=0.391). The distribution per quadrant, regardless of the age group at first calving was: Quadrant I (52/150, 34.7 %); Quadrant II (42/150, 28.0 %); Quadrant III (28/150; 18.7 %); Quadrant IV (28/150; 18.7 %). Conclusion. Cows located in Quadrant II (negative values of PC1 and positive values of PC2), were efficient in the grazing system, showed greater longevity with productive levels compatible with the limitations of the system, and with an efficient reproductive behavior.